2004
DOI: 10.1139/v03-187
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Suzuki cross-coupling reactions of 4,7-dichloroquinoline and 7-chloro-4-iodoquinoline with arylboronic acids using phosphine-free palladium catalysis in water

Abstract: 4,7-Dichloroquinoline (1a) and 7-chloro-4-iodoquinoline (1b) undergo Suzuki cross-coupling reactions with arylboronic acids catalyzed by phosphine-free palladium acetate in boiling water. Using phenylboronic acid (2), the reaction of 1a provides 7-chloro-4-phenylquinoline (3) (78%) together with diphenylquinoline (4) (12%), while 1b reacts in a much more regioselective fashion and provides 3 in 98% isolated yield. Although 1b undergoes a more regioselective Suzuki reaction than 1a, additional important observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…(Scheme 1) 4,7-dichloroquinoline has been studied by two different groups, with both reporting good selectivity for coupling at the 4 position. 8 In one case, the initial Suzuki coupling at C4 was the followed by a second coupling reaction at C7 to afford product 1 in 69% yield over the two steps. 9 …”
Section: Introductionmentioning
confidence: 99%
“…(Scheme 1) 4,7-dichloroquinoline has been studied by two different groups, with both reporting good selectivity for coupling at the 4 position. 8 In one case, the initial Suzuki coupling at C4 was the followed by a second coupling reaction at C7 to afford product 1 in 69% yield over the two steps. 9 …”
Section: Introductionmentioning
confidence: 99%
“…It has, consequently, been widely applied in the formation of biaryl compounds where it usually involves the Pd(0)-mediated linking of an aryl halide with an arylboronic acid or arylboronate ester. The mechanism by which it proceeds is known to be complex in its details, and the oxidative addition, ,, transmetalation, , and reductive elimination steps have all been reported to be rate-determining in certain cases. Nonetheless, there is broad consensus that the main stages involved are those shown in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…It was also observed that 7‐chloro‐4‐iodoquinoline ( 380 ) underwent Pd(OAc) 2 ‐catalyzed Suzuki–Miyaura monoarylation in a more site‐selective fashion with a variety of (hetero)arylboronic acids and an alkenylboronic acid in the absence of ( n‐ Bu) 4 NBr to give 4‐substituted 7‐chloroquinolines 384 in yields ranging from 58 to 97% (Scheme ). However, the rate of the reaction of 381 with boronic acid 19 was three times lower than that of 372 127…”
Section: Cross‐coupling Reactions Of Polyhalogenated Six‐membered Hmentioning
confidence: 88%
“…In 2004, Friesen and Trimble127 found that 4,7‐dichloroquinoline ( 372 ) underwent Pd(OAc) 2 ‐catalyzed site‐selective arylation at the activated C‐4 position by treatment with 1.1 equiv. of phenylboronic acid ( 19 ) in the presence of 0.25 equiv.…”
Section: Cross‐coupling Reactions Of Polyhalogenated Six‐membered Hmentioning
confidence: 99%